Existence of Solutions to a $p$-Laplacian Equation with Integral Initial Condition (Communications in Mathematical Research, 2019)
In this paper, a class of one-dimension $p$-Laplacian equation with nonlocalinitial value is studied. The existence of solutions to such a problem is obtained byusing the topological degree method.